Gold nanostars mediated combined photothermal and photodynamic therapy and X-ray imaging for cancer theranostic applications. (November 2015) - Wang, Lei; Meng, Dehui; Hao, Yongwei; Zhao, Yalin; Li, Dong; Zhang, Bingxiang; Zhang, Yun; Zhang, Zhenzhong
Gold nanomaterials possess unique physical and chemical properties, which attracted much attention in recent years. As a new type of gold nanomaterials, gold nanostars (GNSTs) have been prepared and characterized in this study. GNSTs under near-infrared (NIR) light irradiation can exert not only cancer photothermal therapy via heat production but also photodynamic therapy via generation of reactive oxygen species. GNSTs were able to enter the cytoplasm as well as nuclei of human breast michigan cancer foundation-7 (MCF-7) cells. Under NIR light irradiation, GNSTs caused more severe DNA damage, arrest the cell cycle in G0/G1 phase, and reduce more cellular glutathione level, causing more severe apoptosis and cell death in vitro. Intratumoral injection of GNSTs with NIR light irradiation significantly inhibited tumor growth in vivo. In addition, GNSTs were demonstrated to be a contrast agent for X-ray imaging. All the in vitro and in vivo results showed that GNSTs can be used for the potential diagnosis and medical treatment of cancer.